Mini-review in scoring systems of UAV sensing by imaging sensors to enhance diagnostic decision making in plant protection - Mokhtari, wafaa; Achouri, Mohamed; chtaina, noureddine; Wahba, Mohamed (European Journal of Applied Sciences, 2021)
The intensive and non-efficient use of pesticides application in agriculture have been causing so far negative impact on water resource contamination and water loss costs (preventive treatment etc). Conventional diagnostic (field scouting, cultivation, microscopy identification, Koch postulate verification etc.) have assisted farmers and diagnostician stakeholders in the consistency of chemical treatment decision up today. Actually, traditional diagnostic is the pillar of decision making in plant protection. Nowadays sustainable water use is a priority under the facts of water scarcity in arid and semi-arid areas especially in the African countries under climate change context. Therefore, to improve water quality and its efficiency, decision making in plant protection in agricultural field and landscapes is moving its strategies towards using advanced yet accessible technologies in disease/pest’s diagnostic. UAV is one of those proximal yet classified into remote sensing devices as well and these technologies help moving diagnostic making decision from laboratory testing out puts to field-testing to enable rapid decision making in plant diseases/pests management at point of care (POC). This tool is even small as it looks ,but it is starting to become a cost and time saving and reducing drudgery in the applications for front line actors (for farmers, and first detectors) in the agriculture production system or in the landscape management. This mini-overview is about providing fundamental and pedagogical support on UAV technologies and application used in plant protection to first detectors. In this terms, a small introduction to proximal sensing of plant diseases as a special recent advanced technique and applications with cases studies will be presented.